Electrochemical Detection of 2, 4‐Dichlorophenol on a Ternary Composite Electrode of Diamond, Graphene, and Polyaniline. Issue 5 (10th February 2017) - Peleyeju, Moses G.; Idris, Azeez O.; Umukoro, Eseoghene H.; Babalola, Jonathan O.; Arotiba, Omotayo A.
Abstract: In this work, a novel ternary composite electrode made from diamond, graphene, and polyaniline was prepared, characterized, and applied for the electrochemical determination of 2, 4‐dichlorophenol (2, 4‐DCP) in aqueous media. The composite obtained through oxidative polymerization of aniline in the presence of graphene and diamond was characterized by Fourier transform infrared spectroscopy, Raman spectroscopy, X‐ray diffraction, andBrunauer−Emmett−Teller surface area analysis . A glassy carbon electrode (GCE) was modified with the composite material and the electrochemical properties of the bare and modified electrodes were investigated by using cyclic voltammetry, square wave voltammetry, and electrochemical impedance spectroscopy. The obtained results show that the modified electrode exhibits superior electrochemical properties to the bare GCE. Determination of 2, 4‐DCP in 0.1 M HNO3 was carried out by using square wave voltammetry, and the oxidation peak of the analyte was found to increase linearly with increasing concentration. The linear regression equation was y = 1 . 1075 × 10 - 6 x + 2 . 5840 × 10 - 5 and the detection limit was calculated to be 0.25 μM. The electrode exhibited antifouling capabilities during the electro‐oxidation of 2, 4‐DCP. The sensor was utilized for the detection of 2, 4‐DCP in domestic wastewater and it is believed to hold promise for practical applications. Abstract : No harm no foul : A novel composite of diamond, graphene, and polyaniline is obtained through the oxidative polymerization of aniline in the presence of diamond and graphene. Electro‐oxidation of 2, 4‐dichlorophenol is carried out at the composite material, and the low susceptibility of diamond‐based electrodes to passivation is demonstrated (see picture).